Chemical characterization and antioxidant activity of three medicinal Apiaceae species - ., Maulidiani; Abas, Faridah; Khatib, Alfi; Shaari, Khozirah (Elsevier, 2014)
tCentella asiatica (‘Pegaga’ = Malaysia) is well known plant that has been used as one of the ingredientsin pharmaceutical and cosmetic industries. Using liquid chromatography with diode array and elec-trospray ionization/mass spectrometry (LC–DAD–ESI/MS) analysis, chemical profiling of three differentPegaga extracts (C. asiatica, H. bonariensis and H. sibthorpioides) revealed variations in their metabo-lite profile. Our findings showed that triterpenes of C. asiatica were characterized by the ursane-typetriterpenes (madecassoside, asiaticoside, madecassic acid, and asiatic acid), while the two Hydrocotylespecies consisted of oleanane-type triterpenes (barrigenol derivatives). Other variations are due tothe difference in phenolic and flavonoid constituents. The three Pegaga extracts were also evalu-ated for their total phenolic content (TPC), 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radicals, andxanthine oxidase inhibition (XOI) activities. The results showed that C. asiatica has the most potentantioxidant activity (TPC = 72.09 mg/100 g DW; DPPH = 72.99 mikrog/ml; XOI = 87.68 mikrog/ml) as compared toH. bonariensis (TPC = 28.55 mg/100 g DW; DPPH = 22.43 mikrog/ml; XOI = 32.23 mikrog/ml) and H. sibthorpioides(TPC = 56.23 mg/100 g DW; DPPH = 37.86 mikrog/ml; XOI = 14.73. mikrog/ml).